Kompetensi, Sertifikasi Guru, dan Kualitas Belajar Siswa Sekolah Dasar - Tjatjuk Siswandoko; Ace Suryadi (Jurnal Pendidikan dan Kebudayaan, 2013)
This study aimed to examine the effect of teacher professional certification on the improved teachers’ competencies, and the quality of students’ learning. This cross-sectional survey, has randomly selected a number of primary schools from the West Java sampling frame at the systematic random sampling procedures. Data were collected from the sixth grade students and teachers, and headmasters in each of the selected schools, for which the individual sixth-grade students was the unit of analysis. This study used the production function model in which school leaving examination scores (UASBN) were be used as the criteria, and selected teachers’, students’, and schools’ variables were the predictors in the model. The analysis indicated that the teachers’ certification has hardly ever been able to promote certificate holders’ competencies. The certification has not even enabled the Ministry to map out teachers by competency levels, since a certificate of teachers was hardly determined by the real teachers’ competencies; they were notning more than just a label of teachers’ seniority and credential. As the certificate holders, teachers did not offer a guaranty to create a higher quality of teaching and improve the quality of students’ learning. The study found out that the students’ learning achievement was determined more by the social economic status of students’ family rather than by the actual certification mechanism. This study has recommended the Government to start reviewing and well improve the effectiveness of certification system that would enable the teachers to promote their own competencies and promote students’ learning sustainably.ABSTRAK Studi ini bertujuan untuk mengetahui efek sertifikasi pendidik terhadap kompetensi guru dan kualitas belajar siswa. Studi cross-sectional survey, ini memilih sekolah dasar sampel secara random dari daftar sekolah dasar di Jawa Barat. Semua siswa dan guru kelas VI, kepala sekolah telah dijadikan responden, dan siswa adalah unit analisis dalam penelitian ini. Data dianalisis dengan menggunakan model fungsi produksi pendidikan dengan UASBN sebagai criteria, dan prediktor yang terpilih adalah variable sertifikasi, kompetensi guru, karakteristik siswa, kepala sekolah, dan sekolah itu sendiri. Hasil studi menunjukkan bahwa sertifikasi pendidik baru berfungsi untuk memacu kompetensi guru, bahkan belum mampu memetakan kompetensi guru, sehingga sertifikat yang dimiliki belum sepenuhnya merupakan indikator kompetensi, tetapi justru lebih berfungsi sebagai label dari senioritas guru. Dalam kondisi demikian, guru menjadi sulit mewujudkan prestasi belajar siswa, prestasi belajar siswa pada akhirnya ditentukan oleh SES (social economic status) keluarga dan kualitas sekolah. Oleh karena itu, Pemerintah diharapkan melakukan perbaikan sistem sertifikasi sehingga efeknya lebih signifikan terhadap kompetensi guru maupun prestasi belajar siswa.